2006
DOI: 10.1002/nag.538
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous deformation analysis with second-order finite element meshed block

Abstract: SUMMARYThe discontinuous deformation analysis (DDA) with second-order displacement functions was derived based on six-node triangular mesh in order to satisfy the requirement for the accurate calculations in practical applications. The matrices of equilibrium equations for the second-order DDA were given in detail for program coding. By close comparison with widely used finite element method and closed form solutions, the advantages of the modified DDA were illustrated. The program coding was carried out in C+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 12 publications
(12 reference statements)
0
30
0
Order By: Relevance
“…Clatworthy and Scheele [20] proposed sub-meshing to enhance block deformability. Grayeli and Mortazavi [21] developed a new 2-D DDA method using the six-node triangular elements and achieved a very good agreement between the analytical and numerical results produced by the modified DDA.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Clatworthy and Scheele [20] proposed sub-meshing to enhance block deformability. Grayeli and Mortazavi [21] developed a new 2-D DDA method using the six-node triangular elements and achieved a very good agreement between the analytical and numerical results produced by the modified DDA.…”
Section: Introductionmentioning
confidence: 72%
“…In 2-D, Grayeli and Mortazavi [21] modified DDA using the high-order triangular finite elements. The basic three-dimensional elements in finite element method (FEM) are the tetrahedron element and the hexahedron element [37].…”
Section: Merging Finite Element Mesh Into a Blockmentioning
confidence: 99%
“…six-noded) triangular elements which are suitable to simulate blocks of any arbitrary shape. Grayeli and Mortazavi (2006) verified their implementation against the Kirsch solution for the displacement field around a circular cavity in an infinite elastic medium. Their results indicated that their DDA approach predicted the elastic deformations around the circular cavity with reasonable accuracy.…”
Section: Introductionmentioning
confidence: 96%
“…Grayeli and Mortazavi (2006) as well as Grayeli and Hatami (2008) present the finite element derivations for the implementation of FEM/DEM in DDA. In this formulation, the blocks are discretised internally using linear elastic, quadratic (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…One method is to glue small blocks together to form a larger block using artificial joints [3][4][5] and sub-blocks [6][7][8]. Some researchers added finite element meshes to the blocks so that stress variations within the blocks can be accounted for [9][10][11][12]. Moreover, Shi's recent development, the numerical manifold method (NMM), was aimed at describing stress distributions within the 1524 S. A. R. BEYABANAKI, A. JAFARI AND M. R. YEUNG…”
Section: Introductionmentioning
confidence: 99%